Normative Data for 84 UK English Rebus Puzzles - Threadgold, Emma; Marsh, John E.; Ball, Linden J. (Frontiers in Psychology, 2018)
Recent investigations have established the value of using rebus puzzles in studying the insight and analytic processes that underpin problem solving. The current study sought to validate a pool of 84 rebus puzzles in terms of their solution rates, solution times, error rates, solution confidence, self-reported solution strategies and solution phrase familiarity. All of the puzzles relate to commonplace English sayings and phrases in the United Kingdom. Eighty-four rebus puzzles were selected from a larger stimulus set of 168 such puzzles and were categorized into six types in relation to the similarity of their structures. The 84 selected problems were thence divided into two sets of 42 items (Set A and Set B), with rebus structure evenly balanced between each set. Participants (N = 170; 85 for Set A and 85 for Set B) were given 30 seconds to solve each item, subsequently indicating their confidence in their solution and self-reporting the process used to solve the problem (analysis or insight), followed by the provision of ratings of the familiarity of the solution phrases. The resulting normative data yield solution rates, error rates, solution times, confidence ratings, self-reported strategies and familiarity ratings for 84 rebus puzzles, providing valuable information for the selection and matching of problems in future research.